Vérification des structures proposées pour la ferrihydrite par diffraction des rayons X des nanoparticules - Meunier, Jean-François (University of Ottawa (Canada), 2010)
Ferrihydrite is a natural iron hydroxide occurring mostly in surface waters. In the last 40 years, six different structures have been proposed for ferrihydrite, without reaching consensus in the scientific community. The contradictory debate around the nanostructure of ferrihydrite represents the principal motivation of the present thesis, i.e., to verify systematically all structure proposals instead of just the most accepted ones. We compare powder x-ray diffraction patterns recorded from synthetic samples of 2-lines and 6-lines ferrihydrite with the calculated ones (Debye sum) from the proposed structures. The comparisons show that all structure propositions are incorrect. Although, three of the six propositions suggest jointly that oxygen atoms form a double-hexagonal close packing structure in ferrihydrite and that the exact structure determination problem could be solved by finding the correct positions of the iron atoms inside the oxygen layers.
Keywords: Nanoscience.; Physics, Condensed Matter.